(untitled) (Anclajes, 2022)
This paper proposes to address the various temporalities that Lola Arias’s biodramatic project on the Malvinas War (the video installation Veterans, the documentary play Minefield and the film Theater of War) brings into play, in relation to the problems associated with temporality that are specific to the narrative of war in general and the Malvinas War in particular. In the first place, each of the works that make up the project is considered as an update of a power (Paolo Virno). Secondly, both the project as a whole and some of its scenes are approached as devices that allow to display what Didi-Huberman calls the fecundity of anachronism. The objective is to think about the novelty that this project introduces in relation to the anachronism that the combatants, designated at the same time as "war boys" and veterans, embody, and which translates into an image in their heads that, in a way of iteration characteristic of the trauma, is neither forgotten nor changed.